A phase II trial to evaluate the combination of pixantrone and obinutuzumab for patients with relapsed aggressive lymphoma: Final results of the prospective, multicentre GOAL trial. (1st April 2022) - Hess, Georg; Hüttmann, Andreas; Witzens‐Harig, Mathias; Dreyling, Martin H.; Keller, Ulrich; Marks, Reinhard; Ernst, Thomas; Pott, Christiane; Viardot, Andreas; Frontzek, Fabian; Trautmann, Marcel; Ruckes, Christian; et al.
Summary: The prognosis of patients with relapsed diffuse large B‐cell lymphoma (DLBCL) remains poor with current options. Here we prospectively evaluated the combination of pixantrone with obinutuzumab for up to six cycles for patients with relapsed or refractory DLBCL. Overall response rate (ORR) was the primary end‐point. Sixty‐eight patients were evaluated, median age was 75 years, median number of prior lines was three (range 1–10), 52 patients (76.5%) were diagnosed with DLBCL and 16 (23.5%) patients had transformed indolent lymphoma or follicular lymphoma (FL) IIIB. ORR was 35.3% for all and 40% for evaluable patients (16.6% complete response), median progression‐free survival (PFS) and overall survival (OS) were 2.8 months and 8 months, respectively. Analysis of the cell of origin revealed a superior course for patients with non‐GCB (germinal centre B‐cell‐like) phenotype [median OS not reached (n.r.) vs 5.2 months]. Patients with one prior line had an improved outcome over patients treated in later lines (PFS n.r. vs 2.5 months). Disease progression was the main reason for premature termination. Adverse events were mainly haematologic. The combination treatment revealed no unexpected adverse events. Most relevant non‐haematologic toxicity was infection in 28% of patients. In summary, pixantrone–obinutuzumab showed clinical activity with sometimes long‐term remission; however, the trial failed to meet its primary end‐point.